Information Management: the Key Driver of the Economic System’s Development - Robert Bacho; Бачо Роберт; Bacsó Róbert; Pukala Ryszard; Пукала Ришард; Hlibko Serhii; Глібко Сергій; Vnukova Nataliya; Внукова Наталія; Vnukova Natália; Peter Pola; Póla Péter; et al. (Sumy State University, 2019)
Abstract. In the scientific article, an information management model was developed for assessing the influence of regulatory tools on business processes on the example of the insurance market of Ukraine. The main purpose of the research is to determine the role of information management as a key driver of business process development in economic systems (on the example of the Ukrainian insurance market). Systematization literary sources and approaches for solving the problem indicates that the development of innovative tools of public governance for the assessment of the regulatory influence of the state regulatory body on the business processes of insurance market is not completed and requires a more in-depth study. The formation of a system of indicators characterizing the business processes of insurance market, which take into account the influence of the Regulator's tools, is proposed to be implemented in the following sequence: to find out the causal links between the indicators of business processes of insurance market and the measures; to determine the existence of the reaction of business processes’ indicators of insurance market to the Regulator’s measures, taking into account the time gap, which determines the presence of lags in the process of applying the Regulator's measures; to define and formalize the variability of the business processes’ indicators of insurance market under the influence of the Regulator's measures. Then the scale of the state of insurance market was built: firstly, check for normality the distribution of the indicators’ values of these markets; secondly, in compliance with the distribution law to construct the scale of indicators according to the «three-sigma rule»; thirdly, in the case of nonconformance with the normal distribution law and presence of skewness, the method of «three sigma» may be used, but either the arithmetic mean, or the mode of the variation series, or its median, is taken as the reference point. The relevance of the decision of this scientific problem is that a set of models is developed for establishing causal relationships between the indicators characterizing the business processes of the insurance market and government regulation instruments, which are quantitatively determined, are theoretical and practical basis for their possible application for solving universal modeling problems of causal processes of estimating the influence of the taken decisions at any regulation of business processes. To solve the problem the Granger-test, the expanded Dickey-Fuller test, the Phillips-Perron test and the Kwiatkowski-Phillips-Schmidt-Shin test were applied. Time series distribution on stationarity and construction of vector autoregression models are implemented. In order to evaluate the adequacy of the models, a comparison of values of Fisher's, Student's criteria, determination coefficient and adjusted determination coefficient is used. Jarque-Bera criteria are used to test the model for stationarity, stability. The formalization of cause-and-effect relationships through the postulate of the theory of measurements and the construction of scales is performed. The built interval scales are based on the application of the three sigma rule, which made possible to specify the allowable boundary values of the indicators. The obtained results testify the influence of regulatory tools on the business processes of insurance market, which confirms the correctness of the use of this complex of models for the solution of weakly formalized problems of causal nature of universal type. The proposed innovative model can be used as a methodology for developing a set of rational methods for assessing informational influences of management decisions in production systems or marketing research. The results of the research can be used to evaluate the business processes of any market or system. Keywords: business processes, Granger test, informational management, informational model, insurance key driver, services market, regulation tools, scaling, vector autoregression.

Резюме. У науковій статті було розроблено інформаційну модель оцінки управління та впливу регуляторних інструментів на бізнеспроцеси на прикладі страхового ринку України. Основна мета дослідження – визначити роль інформаційного менеджементу як ключового рушія розвитку бізнес-процесів в економічних системах (на прикладі страхового ринку України). Систематизація літературних джерел та підходів до вирішення проблеми свідчить про те, що розробка інноваційних інструментів оцінки регуляторного впливу органу державного регулювання на бізнес-процеси страхового ринку не завершена і потребує більш поглибленого вивчення.Формування системи показників стану страхового ринку, які враховують вплив інструментів Регулятора, запропоновано реалізувати у такій послідовності: виявити наявність причинно-наслідкових зв’язків між показниками стану страхового ринку та заходами регулювання (впливу); визначити наявність реакції показників стану страхового ринку на заходи Регулятора з урахуванням розриву в часі, що обумовлює наявності лагів у процесі застосування заходів Регулятора; означити та формалізувати змінність показників стану страхового ринку під впливом заходів Регулятора. В результаті були сформульовані завдання щодо шкали стану страхового ринку: по-перше, перевірити на нормальність розподіл значень показників його стану; по-друге, побудувати відповідно до закону розподілу шкалу показників за правилом «трьох сигм»; по-третє, у разі невідповідності нормальному закону розподілу та наявності асиметрії можливе використання методу «трьох сигм», але за точку відліку береться або середнє арифметичне, або мода варіаційного ряду, або його медіана. Актуальність рішення цієї наукової проблеми полягає в тому, що розроблено комплекс моделей для встановлення причиннонаслідкових залежностей між показниками, що характеризують стан страхового ринку та інструментами державного регулювання, які визначено кількісно, і є теоретичною та практичною базою для можливого їх вживання для вирішення універсальних задач моделювання причинно-наслідкових процесів оцінки впливу прийнятих рішень під час будь-якого регулювання розвитку систембізнес-процесів. Для вирішення завдання проведено тест Грейнджера, розширений тест ДіккіФуллєра, тест Філліпса-Перрона та тест Квятковського-Філліпса-Шмідта-Шина. Виконано розподіл часових рядів за стаціонарністю, здійснена побудова моделей векторної авто регресії. Для оцінювання адекватності моделей використано порівняння значень критерію Фішера, Ст’юдента, коефіцієнта детермінації та скорегованого коефіцієнта детермінації. Для перевірки моделі на стаціонарність, стабільність використано критерії Jarque-Bera. Виконано формалізацію причиннонаслідкових зв’язків через постулат теорії вимірів і побудови шкал. Побудовані інтервальні шкали ґрунтуються на застосуванні правила «трьох сигм», що дозволило означити гранично допустимі значення показників. Отримані результати свідчать про вплив регуляторних інструментів на бізнес-процеси страхового ринку, що підтверджує правильність використання цього комплексу моделей для вирішення слабо формалізованих задач причинного характеру універсального типу. Запропонована інноваційна модель може бути використана як методологія розробки набору раціональних методів оцінки інформаційних впливів управлінських рішень у виробничих системах або маркетингових дослідженнях. Результати дослідження можуть бути використані для оцінки бізнес-процесів будь-якого ринку чи системи.
Інформаційний менеджмент ключовий драйвер розвитку економічних систем
Редакційна колегія: https://mmi.sumdu.edu.ua/editorial-board/
Зміст: https://mmi.sumdu.edu.ua/volume-10-issue-3/
Keywords: business processes; Granger test; informational management; informational model; informational model; insurance key driver; services market; regulation tools; scaling; vector autoregression